Obraz przeszłości Kożuchowa w wybranej historiografii miasta. Przyczynek do badań nad problematyką badań miast współczesnego regionu lubuskiego = An image of the Kożuchów`s past in a selected historiography of the city. Contribution to research on the issues of urban research tin the contemporary Lubuskie region - Klecha-Zygadło, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses selected publisher from regional historiography devoted to the city of Kożuchów, issued since 1945. The 1aim of the article is an attempt to assess to what extent post- war and contemporary research differ in terms of methodological approaches. Therefore, not only the selected content is important, but most importantly, the questions about the city`s approach itself (here Kożuchów) as a complex research structure.
Keywords: miasto; region; historiografia; historia; city; historiography; history